Presenting a Model for Training Reflective Managers for Farhangian University - Mohammad Ahmadi beni; Masoumeh Oladian; Mahmoud Safari (Iranian Journal of Educational Research)
Objective: In contemporary academia, a significant number of higher education institutions have increasingly focused on the training and development of their managerial personnel to effectively address their administrative requirements. Given that the leaders and managers serve as both the driving force and guiding mechanism of universities, enhancing and fostering the behavioral and specialized competencies of these managers profoundly influences their overall performance. The objective of the present investigation is to propose a framework for the cultivation of reflective managers specifically for Farhangian University. Methods: This research is categorized as applied in terms of its objectives and employs Grounded Theory as its methodological approach. The data collection process involved semi-structured interviews conducted with fifteen professors and administrators from Farhangian University, who were selected through purposive sampling techniques. The analysis of the research data was conducted utilizing a database theory approach, which included open, axial, and selective coding, facilitated by MAXQDA software. Results: The resultant paradigm model, centered on the phenomenon of reflective thinking development, serves to assist managers in enhancing their reflective thinking attributes. Furthermore, the proposed model encompasses strategies for the advancement of reflective managers influenced by causal factors (such as educational influences, development opportunities, critical reflective thinking, and the personality traits and skills of managers), contextual factors (which include access to university infrastructure, the cultural milieu of the university, and support from higher-level organizations), as well as various intervening variables. These intervening variables consist of managers' knowledge, self-awareness, and critical understanding. Conclusions: These empirical results have the potential to guide the formulation and execution of methodologies designed for the training of reflective managers.